High-strength anti-fog glass and method for producing the same

CN122685313BActive Publication Date: 2026-10-23LONGGUANGTIANXU SOLAR ENERGY ZHUCHENG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611126152.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-23
Estimated Expiration
2046-07-28

AI Technical Summary

Technical Problem

[0004]综上所述,目前现有的技术方案虽然在一定程度上对防雾玻璃的某些性能进行了改进,但仍存在以下技术问题:机械性能差、防雾性能差、长效防雾性能不足

Benefits of technology

(1)本发明通过引入含二氧化钛、二氧化铈、氧化铌的协同防雾助剂,将亲水性金属离子均匀引入玻璃体系。Ti4+部分作为网络中间体,Nb5+作为网络修饰体,增强玻璃表面的极性,提高对水分子的吸附能力,降低水接触角。引入的ZrO2可增强网络骨架强度,而Nb2O5与B2O3共同作用,在提高化学稳定性的同时优化了离子交换通道的微观结构,使钾离子能够有效交换进入表层,形成厚度适中、均匀稳定的表面压应力层,从而在不过分阻碍离子扩散的前提下协同提升抗冲击与抗划伤能力。玻璃基体的本征亲水性可提升亲水涂层与玻璃表面的界面结合力,增强涂层附着力;同时当涂层出现局部磨损时,暴露的玻璃基体仍可保持一定的亲水铺展能力,避免局部起雾,与表面涂覆层共同构成长效防雾体系。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122685313B_ABST
    Figure CN122685313B_ABST
Patent Text Reader

Abstract

The application discloses high-strength anti-fog glass and a preparation method thereof, and relates to the technical field of glass preparation. The preparation method of the glass comprises the steps of preparing a synergistic anti-fog auxiliary agent, mixing and melting glass raw materials, ion exchange strengthening, preparing a coating liquid, and obtaining a finished product glass. The glass comprises a glass layer and a coating layer. The raw materials of the glass layer comprise silicon dioxide, sodium carbonate, calcium carbonate, magnesium oxide, aluminum oxide, boron oxide, zirconium dioxide and the synergistic anti-fog auxiliary agent. The raw materials of the synergistic anti-fog auxiliary agent comprise titanium dioxide, cerium dioxide and niobium oxide. The raw materials of the coating layer comprise carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid and sodium polyacrylate. The anti-fog glass prepared by the application has high mechanical strength, good anti-fog performance and excellent long-acting anti-fog performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass manufacturing technology, specifically to a high-strength anti-fog glass and its manufacturing method. Background Technology

[0002] Anti-fog glass is widely used in bathroom mirrors, kitchen glass, and optical instrument covers because it can effectively prevent blurred vision caused by water vapor condensation. These applications not only require the glass to have stable anti-fog performance, but also good mechanical strength to withstand high-frequency use such as daily wiping and minor impacts.

[0003] Currently, existing anti-fog glass technologies have significant shortcomings: On the one hand, traditional anti-fog solutions mostly rely on a single hydrophilic coating, which can achieve short-term anti-fog properties, but the coating has poor abrasion resistance and is prone to peeling off and failure after repeated cleaning, resulting in a short anti-fog lifespan; on the other hand, most anti-fog glasses prioritize anti-fog functionality, often neglecting strength optimization. The added anti-fog additives can easily damage the glass matrix network structure, leading to reduced glass hardness and poor impact resistance. Even the few solutions that use physical tempering or other strengthening processes suffer from complex processes, high costs, or the potential for reduced light transmittance. Existing technology with publication number CN111960689A discloses a manufacturing process for anti-fog tempered glass. This existing technology mainly relies on physical tempering to improve strength, with limited improvement in bending strength and impact resistance. The anti-fog mechanism relies on a surface-sprayed polyethylene glycol acrylate coating, which easily fails to provide long-term anti-fog performance after coating wear. The prior art disclosed in CN109734325A is a method for preparing superhydrophobic antifog glass. This prior art relies solely on the physical adsorption of epoxy resin emulsion to the glass surface. In humid environments, the coating is prone to blistering and peeling. In addition, it lacks a strength-enhancing design, and even slight daily friction will damage the rough structure of the coating, resulting in poor overall scratch resistance and impact resistance of the glass.

[0004] In summary, although the existing technical solutions have improved some properties of anti-fog glass to a certain extent, the following technical problems still exist: poor mechanical properties, poor anti-fog performance, and insufficient long-term anti-fog performance. Summary of the Invention

[0005] In order to solve the above-mentioned problems in the prior art, the present invention provides a high-strength anti-fog glass and its preparation method, and achieves the following objectives: to prepare anti-fog glass with high mechanical strength, good anti-fog performance and excellent long-term anti-fog performance.

[0006] To achieve the above objectives, the following technical solution is adopted: A method for preparing high-strength anti-fog glass includes the following steps: preparing a synergistic anti-fog additive, mixing and melting glass raw materials, ion exchange strengthening, preparing a coating solution, and obtaining the finished glass.

[0007] The preparation of the synergistic anti-fogging additive involves: mixing titanium dioxide, cerium dioxide, and niobium oxide evenly, heating to 1350-1400℃, and holding at that temperature for 3-4 hours; after the holding period, naturally cooling to room temperature, then pulverizing using a crusher and ball mill, and passing through a 200-mesh sieve to obtain the synergistic anti-fogging additive.

[0008] From the appendix Figure 1 It is evident that the Ti, Nb, and Ce elements in the synergistic antifogging additive are uniformly distributed in the powder without obvious local enrichment or segregation, indicating that titanium dioxide, cerium dioxide, and niobium oxide achieved good component homogeneity after high-temperature calcination, pulverization, and sieving.

[0009] Furthermore, the mass ratio of titanium dioxide, cerium dioxide, and niobium oxide is (5-10):(5-8):(1-3).

[0010] The glass raw material mixing and melting process involves uniformly mixing silica, sodium carbonate, calcium carbonate, magnesium oxide, aluminum oxide, boron oxide, zirconium dioxide, and a synergistic anti-fogging agent, pouring the mixture into a corundum crucible, placing it in a glass melting furnace, heating to 1200-1250℃, and holding at that temperature for 2-2.5 hours; then heating to 1500-1550℃ and melting for 4-5 hours; cooling to 1440-1450℃ and holding at that temperature for 60-70 minutes to homogenize, yielding molten glass. The mold is preheated to 580-600℃, and then the molten glass is poured into the mold and gently pressed to form the shape. The formed glass plate is then transferred to an annealing furnace for annealing treatment to obtain the glass matrix.

[0011] Furthermore, the raw materials are formulated in the following weight ratios: 65-72 parts silica, 17-20 parts sodium carbonate, 16-20 parts calcium carbonate, 3-4 parts magnesium oxide, 3-4 parts aluminum oxide, 0.5-0.8 parts boron oxide, 0.5-0.8 parts zirconium dioxide, and 1.5-2 parts synergistic anti-fogging agent. The annealing treatment involves holding at 500-550℃ for 2-2.5 hours, then cooling to room temperature at a rate of 5-10℃ / h.

[0012] The ion exchange strengthening process involves melting potassium nitrate at 450-480℃ and stirring for 15-20 minutes at a speed of 50-100 rpm to obtain an ion exchange molten salt. A dried glass substrate is then immersed in the ion exchange molten salt and treated at a constant temperature. It is then slowly cooled to room temperature in the furnace, and residual salt stains on the surface are washed with deionized water. Finally, it is dried at room temperature to obtain a glass substrate.

[0013] Furthermore, the constant temperature treatment involves controlling the temperature at 450-480℃ and maintaining the temperature for 8-10 hours.

[0014] Preparation of the coating solution: Nano-cerium dioxide is added to an ethanol aqueous solution to obtain a cerium dioxide suspension; after ultrasonic dispersion, tetraethyl orthosilicate is added dropwise. After the addition is complete, the pH value is adjusted to 8-9 with ammonia water, the temperature is 40-50℃, and the reaction is stirred for 2-3 hours at a speed of 200-300 rpm; after the reaction is completed, the solid is collected by centrifugation, washed 3-4 times with deionized water, and dried to obtain modified cerium dioxide.

[0015] From the appendix Figure 2 As can be seen, the modified cerium dioxide particles exhibit a clear core-shell structure; the coating layer is uniform in thickness and continuous and complete, proving that nano-cerium dioxide with modified silica surface was successfully prepared by coating with tetraethyl orthosilicate hydrolysate.

[0016] Carboxymethyl chitosan and citric acid were added to deionized water and stirred until completely dissolved. Modified cerium dioxide, nanocellulose, and sodium polyacrylate were added, and the mixture was ultrasonically dispersed and stirred for 1-2 hours at a speed of 300-400 rpm to obtain the coating solution.

[0017] Furthermore, the mass fraction of cerium dioxide in the cerium dioxide suspension is 5-10%.

[0018] The ethanol-water solution is obtained by mixing anhydrous ethanol and deionized water at a mass ratio of (8-10):1.

[0019] The amount of tetraethyl orthosilicate used is 20-30% of the mass of cerium dioxide.

[0020] The ultrasonic dispersion is performed at a power of 300-500W for 30-40 minutes.

[0021] The drying process involves drying at a temperature of 80-100℃ for 6-8 hours.

[0022] The mass ratio of carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid, sodium polyacrylate, and deionized water is (6-8):(1-2):(1-2):(0.5-1):(0.1-0.3):(100-160).

[0023] The finished glass is obtained by coating the glass substrate with a coating liquid; after coating, it is first dried for 2-3 hours at a temperature of 50-60℃, and then heat-treated for 3-4 hours at a temperature of 130-150℃ to obtain the finished glass.

[0024] Furthermore, the coating process involves uniformly coating the coating liquid onto the surface of the glass substrate using a spraying method, controlling the dry film thickness of the coating layer to be 2-3 μm.

[0025] The beneficial effects of this invention are as follows: (1) This invention introduces hydrophilic metal ions uniformly into the glass system by introducing a synergistic anti-fogging agent containing titanium dioxide, cerium dioxide, and niobium oxide. 4+ Partially acting as a network intermediary, Nb 5+ As a network modifier, it enhances the polarity of the glass surface, improves the adsorption capacity for water molecules, and reduces the water contact angle. The introduced ZrO2 strengthens the network framework, while Nb2O5 and B2O3 work together to improve chemical stability and optimize the microstructure of ion exchange channels, enabling potassium ions to effectively exchange into the surface layer and form a moderately thick, uniform, and stable surface compressive stress layer. This synergistically improves impact and scratch resistance without excessively hindering ion diffusion. The intrinsic hydrophilicity of the glass substrate enhances the interfacial bonding between the hydrophilic coating and the glass surface, strengthening coating adhesion. Simultaneously, when the coating experiences localized wear, the exposed glass substrate retains a certain degree of hydrophilic spreading ability, preventing localized fogging and forming a long-lasting anti-fogging system together with the surface coating.

[0026] The SiO2-modified nano-cerium dioxide in the coating layer can efficiently absorb ultraviolet light while isolating the photocatalytic active centers from the organic matrix, significantly delaying the ultraviolet aging of carboxymethyl chitosan and nanocellulose, and extending the coating's service life. The three-dimensional hydrophilic network constructed by carboxymethyl chitosan and nanocellulose provides a large number of hydroxyl sites, enabling water mist to spread rapidly into a continuous transparent water film; the microstructure formed by nanocellulose can accelerate water film spreading and moisture diffusion, further improving anti-fogging durability.

[0027] (2) The high-strength anti-fog glass of the present invention has high mechanical strength. The finished glass has a bending strength of 613-624 MPa, a hardness of 636-649 Hv, and a minimum breaking height of 75-80 cm.

[0028] (3) The high-strength anti-fog glass of the present invention has excellent anti-fog performance. In the anti-fog performance test, the finished glass was placed in an environment of 20℃ and 50%RH for 1 hour and then placed above warm water at 40℃. The anti-fog time was 164-167 seconds.

[0029] (4) The high-strength anti-fog glass of the present invention has excellent long-term anti-fog performance. After 100 wiping treatments, the anti-fog time of the prepared glass is 147-158s; after 300 wiping treatments, the anti-fog time is 131-139s. Attached Figure Description

[0030] Appendix Figure 1 The image shows a scanning electron microscope-energy dispersive spectroscopy (EDS) analysis of the synergistic antifogging agent prepared in step one of Example 2.

[0031] Appendix Figure 2This is a TEM transmission electron microscope image of the modified cerium dioxide prepared in step four of Example 2. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of the present invention clearer, the embodiments of the present invention will be described in further detail below. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0033] Example 1: A high-strength anti-fog glass and its preparation method A high-strength anti-fog glass, comprising a glass layer and a coating layer.

[0034] The glass layer, by weight, is composed of the following raw materials: 65 parts silicon dioxide, 20 parts sodium carbonate, 16 parts calcium carbonate, 4 parts magnesium oxide, 3 parts aluminum oxide, 0.8 parts boron oxide, 0.5 parts zirconium dioxide, and 2 parts synergistic anti-fogging agent.

[0035] The coating layer uses raw materials including carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid, and sodium polyacrylate.

[0036] A method for preparing high-strength anti-fog glass includes the following steps: Step 1: Preparation of synergistic anti-fogging additives Titanium dioxide, cerium dioxide, and niobium oxide were mixed evenly and heated to 1350℃ and kept at that temperature for 4 hours. After the heating was completed, the mixture was allowed to cool naturally to room temperature. Then, it was crushed using a crusher and a ball mill and passed through a 200-mesh sieve to obtain a synergistic anti-fogging additive.

[0037] The mass ratio of titanium dioxide, cerium dioxide, and niobium oxide is 5:5:1.

[0038] Step 2: Mixing and Melting Glass Raw Materials Silica, sodium carbonate, calcium carbonate, magnesium oxide, aluminum oxide, boron oxide, zirconium dioxide, and a synergistic anti-fogging agent were mixed evenly and poured into a corundum crucible. The crucible was then placed in a glass melting furnace and heated to 1200℃, holding for 2.5 hours. The temperature was then increased to 1500℃ and melted for 5 hours. The mixture was then cooled to 1440℃ and held for 70 minutes to homogenize, yielding molten glass. The mold was preheated to 580℃, and the molten glass was poured into the mold and gently pressed to form the glass. The formed glass plate was then transferred to an annealing furnace for annealing treatment to obtain the glass matrix.

[0039] The annealing process involves holding the temperature at 500°C for 2.5 hours, and then cooling it to room temperature at a rate of 5°C / hour.

[0040] Step 3: Ion exchange enhancement Potassium nitrate was heated to molten at 450°C and stirred for 20 minutes at 50 rpm to obtain an ion-exchange molten salt. The dried glass substrate was immersed in the ion-exchange molten salt and treated at a constant temperature. Then, it was slowly cooled to room temperature in the furnace, and the surface residual salt was washed with deionized water. The substrate was then dried at room temperature to obtain a glass substrate.

[0041] The constant temperature treatment: the temperature is controlled at 450℃ and the constant temperature treatment lasts for 10 hours.

[0042] Step 4: Preparation of Coating Solution Nano-cerium dioxide was added to an aqueous ethanol solution to obtain a cerium dioxide suspension; after ultrasonic dispersion, tetraethyl orthosilicate was added dropwise. After the addition was complete, the pH value was adjusted to 8 with ammonia water, the temperature was 40℃, and the reaction was stirred for 3 hours at a speed of 200 rpm; after the reaction was completed, the solid was collected by centrifugation, washed 3 times with deionized water, and dried to obtain modified cerium dioxide.

[0043] Carboxymethyl chitosan and citric acid were added to deionized water and stirred until completely dissolved. Modified cerium dioxide, nanocellulose, and sodium polyacrylate were added, and the mixture was ultrasonically dispersed and stirred for 1 hour at a speed of 400 rpm to obtain the coating solution.

[0044] The cerium dioxide suspension contains 5% cerium dioxide by mass.

[0045] The ethanol-water solution is obtained by mixing anhydrous ethanol and deionized water at a mass ratio of 8:1.

[0046] The amount of tetraethyl orthosilicate used is 20% of the mass of cerium dioxide.

[0047] The ultrasonic dispersion was performed at a power of 300W for 40 minutes.

[0048] The drying process involves drying at 80°C for 8 hours.

[0049] The mass ratio of carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid, sodium polyacrylate, and deionized water is 6:1:1:0.5:0.1:100.

[0050] Step 5: Obtain the finished glass The glass substrate is coated with a coating solution. After coating, it is dried for 2 hours at 60°C and then heat-treated for 3 hours at 150°C to obtain the finished glass.

[0051] The coating process involves uniformly coating the coating liquid onto the surface of the glass substrate using a spraying method, with the dry film thickness of the coating layer controlled to be 2 μm.

[0052] Example 2: A high-strength anti-fog glass and its preparation method A high-strength anti-fog glass, comprising a glass layer and a coating layer.

[0053] The glass layer, by weight, is composed of the following raw materials: 68 parts silicon dioxide, 19 parts sodium carbonate, 18 parts calcium carbonate, 4 parts magnesium oxide, 3 parts aluminum oxide, 0.6 parts boron oxide, 0.7 parts zirconium dioxide, and 2 parts synergistic anti-fogging agent.

[0054] The coating layer uses raw materials including carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid, and sodium polyacrylate.

[0055] A method for preparing high-strength anti-fog glass includes the following steps: Step 1: Preparation of synergistic anti-fogging additives Titanium dioxide, cerium dioxide, and niobium oxide were mixed evenly and heated to 1380℃ and kept at that temperature for 3.5 hours. After the heating was completed, the mixture was allowed to cool naturally to room temperature. Then, it was crushed using a crusher and a ball mill and passed through a 200-mesh sieve to obtain a synergistic anti-fogging additive.

[0056] The mass ratio of titanium dioxide, cerium dioxide, and niobium oxide is 8:6:2.

[0057] Step 2: Mixing and Melting Glass Raw Materials Silica, sodium carbonate, calcium carbonate, magnesium oxide, aluminum oxide, boron oxide, zirconium dioxide, and a synergistic anti-fogging agent were mixed evenly and poured into a corundum crucible. The crucible was then placed in a glass melting furnace and heated to 1230℃, holding for 2.5 hours. The temperature was then increased to 1520℃ and melted for 4.5 hours. The mixture was then cooled to 1440℃ and held for 60 minutes to homogenize, yielding molten glass. The mold was preheated to 590℃, and the molten glass was poured into the mold and gently pressed to form the glass. The formed glass plate was then transferred to an annealing furnace for annealing treatment to obtain the glass matrix.

[0058] The annealing process involves holding the temperature at 530°C for 2.5 hours, and then cooling it to room temperature at a rate of 8°C / hour.

[0059] Step 3: Ion exchange enhancement Potassium nitrate was melted at 460°C and stirred for 18 minutes at 100 rpm to obtain an ion-exchange molten salt. The dried glass substrate was immersed in the ion-exchange molten salt and treated at a constant temperature. Then, it was slowly cooled to room temperature in the furnace, and the surface residual salt was washed with deionized water. The substrate was then dried at room temperature to obtain a glass substrate.

[0060] The constant temperature treatment: the temperature is controlled at 470℃ and the constant temperature treatment lasts for 9 hours.

[0061] Step 4: Preparation of Coating Solution Nano-cerium dioxide was added to an aqueous ethanol solution to obtain a cerium dioxide suspension; after ultrasonic dispersion, tetraethyl orthosilicate was added dropwise. After the addition was complete, the pH value was adjusted to 8.5 with ammonia water, the temperature was 45℃, and the reaction was stirred for 2.5 h at a speed of 300 rpm; after the reaction was completed, the solid was collected by centrifugation, washed 4 times with deionized water, and dried to obtain modified cerium dioxide.

[0062] Carboxymethyl chitosan and citric acid were added to deionized water and stirred until completely dissolved. Modified cerium dioxide, nanocellulose, and sodium polyacrylate were added, and the mixture was ultrasonically dispersed and stirred for 1.5 hours at a speed of 400 rpm to obtain the coating solution.

[0063] The cerium dioxide suspension contains 8% cerium dioxide by mass.

[0064] The ethanol-water solution is obtained by mixing anhydrous ethanol and deionized water at a mass ratio of 9:1.

[0065] The amount of tetraethyl orthosilicate used is 25% of the mass of cerium dioxide.

[0066] The ultrasonic dispersion was performed at a power of 400W for 35 minutes.

[0067] The drying process involves drying at 90°C for 7 hours.

[0068] The mass ratio of carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid, sodium polyacrylate, and deionized water is 7:1.5:1.5:0.8:0.1:130.

[0069] Step 5: Obtain the finished glass The glass substrate is coated with a coating solution. After coating, it is dried for 2.5 hours at 55°C and then heat-treated for 3.5 hours at 140°C to obtain the finished glass.

[0070] The coating process involves uniformly coating the glass substrate surface with a coating liquid using a spraying method, controlling the dry film thickness of the coating layer to be 3 μm.

[0071] Example 3: A high-strength anti-fog glass and its preparation method A high-strength anti-fog glass, comprising a glass layer and a coating layer.

[0072] The glass layer, by weight, is composed of the following raw materials: 72 parts silicon dioxide, 17 parts sodium carbonate, 20 parts calcium carbonate, 3 parts magnesium oxide, 4 parts aluminum oxide, 0.5 parts boron oxide, 0.8 parts zirconium dioxide, and 1.5 parts synergistic anti-fogging agent.

[0073] The coating layer uses raw materials including carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid, and sodium polyacrylate.

[0074] A method for preparing high-strength anti-fog glass includes the following steps: Step 1: Preparation of synergistic anti-fogging additives Titanium dioxide, cerium dioxide, and niobium oxide were mixed evenly and heated to 1400℃ and kept at that temperature for 3 hours. After the heating was completed, the mixture was allowed to cool naturally to room temperature. Then, it was crushed using a crusher and a ball mill and passed through a 200-mesh sieve to obtain a synergistic anti-fogging additive.

[0075] The mass ratio of titanium dioxide, cerium dioxide, and niobium oxide is 10:8:3.

[0076] Step 2: Mixing and Melting Glass Raw Materials Silica, sodium carbonate, calcium carbonate, magnesium oxide, aluminum oxide, boron oxide, zirconium dioxide, and a synergistic anti-fogging agent were mixed evenly and poured into a corundum crucible. The crucible was then placed in a glass melting furnace and heated to 1250℃ for 2 hours. The temperature was then increased to 1550℃ and melted for 4 hours. The mixture was then cooled to 1450℃ and held for 60 minutes to homogenize, yielding molten glass. The mold was preheated to 600℃, and the molten glass was poured into the mold and gently pressed to form the glass. The formed glass plate was then transferred to an annealing furnace for annealing treatment to obtain the glass matrix.

[0077] The annealing process involves holding the temperature at 550°C for 2 hours, and then cooling it to room temperature at a rate of 10°C / hour.

[0078] Step 3: Ion exchange enhancement Potassium nitrate was heated to 480℃ and melted, then stirred for 15 minutes at 100 rpm to obtain an ion-exchange molten salt. A dried glass substrate was immersed in the ion-exchange molten salt and treated at a constant temperature. It was then slowly cooled to room temperature in the furnace, and residual salt stains on the surface were washed with deionized water. The substrate was then dried at room temperature to obtain a glass substrate.

[0079] The constant temperature treatment: the temperature is controlled at 480℃ and the constant temperature treatment lasts for 8 hours.

[0080] Step 4: Preparation of Coating Solution Nano-cerium dioxide was added to an ethanol aqueous solution to obtain a cerium dioxide suspension; after ultrasonic dispersion, tetraethyl orthosilicate was added dropwise. After the addition was complete, the pH value was adjusted to 9 with ammonia water, the temperature was 50℃, and the reaction was stirred for 2 hours at a speed of 300 rpm; after the reaction was completed, the solid was collected by centrifugation, washed 4 times with deionized water, and dried to obtain modified cerium dioxide.

[0081] Carboxymethyl chitosan and citric acid were added to deionized water and stirred until completely dissolved. Modified cerium dioxide, nanocellulose, and sodium polyacrylate were added, and the mixture was ultrasonically dispersed and stirred for 2 hours at 300 rpm to obtain the coating solution.

[0082] The cerium dioxide suspension contains 10% cerium dioxide by mass.

[0083] The ethanol-water solution is obtained by mixing anhydrous ethanol and deionized water at a mass ratio of 10:1.

[0084] The amount of tetraethyl orthosilicate used is 30% of the mass of cerium dioxide.

[0085] The ultrasonic dispersion was performed at a power of 500W for 30 minutes.

[0086] The drying process involves drying at 100℃ for 6 hours.

[0087] The mass ratio of carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid, sodium polyacrylate, and deionized water is 8:2:2:1:0.3:160.

[0088] Step 5: Obtain the finished glass The glass substrate is coated with a coating solution. After coating, it is dried for 3 hours at 50°C and then heat-treated for 4 hours at 130°C to obtain the finished glass.

[0089] The coating process involves uniformly coating the glass substrate surface with a coating liquid using a spraying method, controlling the dry film thickness of the coating layer to be 3 μm.

[0090] Comparative Example 1 An anti-fog glass includes a glass layer and a coating layer.

[0091] The glass layer, by weight, is composed of the following raw materials: 68 parts silicon dioxide, 19 parts sodium carbonate, 18 parts calcium carbonate, 4 parts magnesium oxide, 3 parts aluminum oxide, 0.6 parts boron oxide, and 0.7 parts zirconium dioxide.

[0092] The coating layer uses raw materials including carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid, and sodium polyacrylate.

[0093] A method for preparing anti-fog glass includes the following steps: Step 1: Mixing and melting glass raw materials Silica, sodium carbonate, calcium carbonate, magnesium oxide, aluminum oxide, boron oxide, and zirconium dioxide were mixed evenly and poured into a corundum crucible. The crucible was then placed in a glass melting furnace and heated to 1230℃, holding for 2.5 hours. The temperature was then increased to 1520℃ and melted for 4.5 hours. The mixture was then cooled to 1440℃ and held for 60 minutes to homogenize, yielding molten glass. The mold was preheated to 590℃, and the molten glass was poured into the mold and gently pressed to form the desired shape. The formed glass plate was then transferred to an annealing furnace for annealing treatment to obtain the glass matrix.

[0094] The annealing process involves holding the temperature at 530°C for 2.5 hours, and then cooling it to room temperature at a rate of 8°C / hour.

[0095] Step 2: Ion exchange enhancement This step is the same as the "ion exchange enhancement" step in Example 2.

[0096] Step 3: Preparation of Coating Solution This step is the same as the "Coating Solution Preparation" step in Example 2.

[0097] Step 4: Obtain the finished glass This step is the same as the "obtaining finished glass" step in Example 2.

[0098] Comparative Example 2 An anti-fog glass, by weight, comprises the following raw materials: 68 parts silicon dioxide, 19 parts sodium carbonate, 18 parts calcium carbonate, 4 parts magnesium oxide, 3 parts aluminum oxide, 0.6 parts boron oxide, 0.7 parts zirconium dioxide, and 2 parts synergistic anti-fog additive.

[0099] A method for preparing anti-fog glass includes the following steps: Step 1: Preparation of synergistic anti-fogging additives This step is the same as the "Preparation of Synergistic Antifogging Agent" step in Example 2.

[0100] Step 2: Mixing and Melting Glass Raw Materials This step is the same as the "glass raw material mixing and melting" step in Example 2.

[0101] Step 3: Ion exchange enhancement This step is the same as the "ion exchange strengthening" step in Example 2, resulting in a glass sample without a coating.

[0102] Example 4 Performance Testing (I) The bending strength of the finished glass samples obtained in Examples 1-3 and Comparative Examples 1-2 was tested. Samples were prepared as specimens 100mm long, 15mm wide, and 1mm thick, using a universal testing machine with a span of 50mm. Hardness testing was performed according to the test methods specified in GB / T 37900-2019, with samples prepared as square specimens with sides of 40mm and a thickness of 1mm. Impact resistance was tested on the finished glass samples. The glass specimens were 0.55mm thick, and a 64g steel ball was dropped from a height of 30cm, with the height increased in increments of 5cm. Three specimens were tested at each height, and the lowest breakage height was recorded. Specific test results are shown in Table 1. Table 1 As shown in Table 1, the finished glass prepared in Examples 1-3 has a bending strength of 613-624 MPa, a hardness of 636-649 Hv, and a minimum fracture height of 75-80 cm. This demonstrates that the high-strength anti-fog glass prepared by this invention has high mechanical strength.

[0103] (ii) The anti-fogging performance of the finished glass prepared in Examples 1-3 and Comparative Examples 1-2 was tested. The finished glass was placed in an environment of 20°C and 50%RH for 1 hour, and then placed above warm water at 40°C, 10 cm above the water surface. The time from the start to fogging was recorded. The specific test results are shown in Table 2.

[0104] Table 2 As shown in Table 2, the finished glass prepared in Examples 1-3 exhibited excellent anti-fog performance. After being placed in an environment of 20°C and 50% RH for 1 hour and then above warm water at 40°C, the anti-fog time was 164-167 seconds. This demonstrates that the high-strength anti-fog glass prepared according to this invention has excellent anti-fog performance.

[0105] (III) The long-term anti-fogging performance of the finished glass prepared in Examples 1-3 and Comparative Examples 1-2 was tested. The glass surface was wiped repeatedly with a lint-free cloth soaked in deionized water at a pressure of 500g. After wiping 100 times and 300 times, the anti-fogging performance was tested (the test method is the same as that in Test (II)). The time from the start to fogging was recorded. The specific test results are shown in Table 3.

[0106] Table 3 As shown in Table 3, the finished glass prepared in Examples 1-3 exhibited an anti-fog time of 147-158 seconds after 100 wiping cycles and 131-139 seconds after 300 wiping cycles. This demonstrates that the high-strength anti-fog glass prepared by this invention possesses excellent long-lasting anti-fog performance.

[0107] Obviously, there are many other possible implementation methods under the concept of this invention. It should be stated here that any changes made under the inventive concept of this invention will fall within the protection scope of this invention.

Claims

1. A high-strength anti-fog glass, characterized in that: The glass includes a glass layer and a coating layer; The raw material composition of the glass layer by weight is as follows: 65-72 parts silicon dioxide, 17-20 parts sodium carbonate, 16-20 parts calcium carbonate, 3-4 parts magnesium oxide, 3-4 parts aluminum oxide, 0.5-0.8 parts boron oxide, 0.5-0.8 parts zirconium dioxide, and 1.5-2 parts synergistic anti-fogging agent; The coating layer is obtained by coating with a coating solution; the coating solution is prepared by adding nano-cerium dioxide to an aqueous ethanol solution to obtain a cerium dioxide suspension; After ultrasonic dispersion, tetraethyl orthosilicate is added dropwise. After the addition is complete, the pH value is adjusted and the reaction is stirred. After centrifugation, washing, and drying, modified cerium dioxide was obtained; carboxymethyl chitosan and citric acid were added to deionized water and stirred until completely dissolved; Modified cerium dioxide, nanocellulose, and sodium polyacrylate were added, ultrasonically dispersed, and then stirred to obtain a coating solution. The synergistic antifog additive is made from titanium dioxide, cerium dioxide, and niobium oxide; the mass ratio of titanium dioxide, cerium dioxide, and niobium oxide is (5-10):(5-8):(1-3).

2. The method for preparing high-strength anti-fog glass according to claim 1, characterized in that: The process includes steps such as preparing a synergistic anti-fogging agent, mixing and melting glass raw materials, ion exchange strengthening, preparing a coating solution, and obtaining finished glass. The preparation of the synergistic anti-fogging additive involves: mixing titanium dioxide, cerium dioxide, and niobium oxide evenly, heating and holding at that temperature; after the holding period, cooling, pulverizing, and sieving to obtain the synergistic anti-fogging additive. The glass raw material mixing and melting process involves uniformly mixing silicon dioxide, sodium carbonate, calcium carbonate, magnesium oxide, aluminum oxide, boron oxide, zirconium dioxide, and a synergistic anti-fogging agent, pouring the mixture into a corundum crucible, placing it in a glass melting furnace, and melting it through stepwise heating to obtain molten glass. The mold is preheated, and the molten glass is poured into the mold and gently pressed to form the shape. The formed glass plate is then annealed to obtain a glass matrix. The ion exchange enhancement involves heating potassium nitrate to melt it and stirring it evenly to obtain an ion exchange molten salt; then immersing a dry glass substrate in the ion exchange molten salt and treating it at a constant temperature. Then, it is cooled, washed with deionized water, and dried to obtain a glass substrate. The coating solution is prepared by adding nano-cerium dioxide to an aqueous ethanol solution to obtain a cerium dioxide suspension; after ultrasonic dispersion, tetraethyl orthosilicate is added dropwise; after the addition is complete, the pH value is adjusted and the reaction is stirred. After centrifugation, washing, and drying, modified cerium dioxide was obtained; carboxymethyl chitosan and citric acid were added to deionized water and stirred until completely dissolved; Modified cerium dioxide, nanocellulose, and sodium polyacrylate were added, ultrasonically dispersed, and then stirred to obtain a coating solution. The finished glass is obtained by coating the glass substrate with a coating liquid, drying it first, and then heat treating it to obtain the finished glass.

3. The method for preparing high-strength anti-fog glass according to claim 2, characterized in that: The stepped heating and melting process involves first heating to 1200-1250℃ and holding for 2-2.5 hours; then heating to 1500-1550℃ and melting for 4-5 hours; finally cooling to 1440-1450℃ and holding for homogenization for 60-70 minutes.

4. The method for preparing high-strength anti-fog glass according to claim 2, characterized in that: The annealing process involves holding the temperature at 500-550℃ for 2-2.5 hours, and then cooling it to room temperature at a rate of 5-10℃ / h.

5. The method for preparing high-strength anti-fog glass according to claim 2, characterized in that: In the preparation step of the coating solution, the mass fraction of cerium dioxide in the cerium dioxide suspension is 5-10%; the ethanol aqueous solution is obtained by mixing anhydrous ethanol and deionized water at a mass ratio of (8-10):

1.

6. The method for preparing high-strength anti-fog glass according to claim 2, characterized in that: In the preparation step of the coating solution, the amount of tetraethyl orthosilicate used is 20-30% of the mass of cerium dioxide.

7. The method for preparing high-strength anti-fog glass according to claim 2, characterized in that: In the preparation step of the coating solution, the mass ratio of carboxymethyl chitosan, modified cerium dioxide, nanocellulose, citric acid, sodium polyacrylate, and deionized water is (6-8):(1-2):(1-2):(0.5-1):(0.1-0.3):(100-160).

8. The method for preparing high-strength anti-fog glass according to claim 2, characterized in that: The coating process involves uniformly coating the glass substrate surface with a coating liquid using a spraying method, controlling the dry film thickness of the coating layer to be 2-3 μm; the heat treatment involves a temperature of 130-150℃ and a time of 3-4 hours.

Citation Information

Patent Citations

  • Production method of superhydrophobic antifog glass

    CN109734325A

  • Preparation process of anti-fog tempered glass

    CN111960689A

  • High-transparent ultraviolet-blocking energy-saving membrane and preparation method thereof by way of phase transfer in solution

    CN101974245A

  • Waterproof high-strength fog and frost resistant coating and preparation method thereof

    CN108410270A